Gastronomical Experiences in the Western Touristic Pole of Portugal - Elias-Almeida, Anabela (2018)
The tourism concept associated to an experience is getting more prominent every day. Food Tourism is one of those expansions of tourism that focuses on the individual as opposed to the world around him. The tourist is the protagonist of an experience, apparently individual, but in reality it involves a whole range of factors, physical and psychological, that do not allow isolating him but identifying him as the one who surrenders to the sensations. According to Fields (2005), gastronomy is run by four pillars that allow tourists to move in certain areas in order to meet their needs. It is the destinations onus to attract tourists with its attributes and its capacity to distinguish itself from other destinations, aiming to provide different experiences. The Western Region through its attributes, either by food associated with the region or some events, allowed us to develop this study, individualizing its characteristics but particularizing the region in a global context. This article results from a research project in the Western Region of Portugal, which had the duration of one year (May 2010 to May 2011), with the objective to understand the role that food tourism plays for the differentiation of a destination, assess the local tourist agents’ perception on food tourism and their sensibility of the same and to profile the food tourist that travels to the Western Touristic Pole and identify key practices of those who travel, motivated by food. Regarding the method of the study, the case study approach was used, with field work that resulted in 863 questionnaire surveys on the demand side and 92 questionnaire surveys on the supply side. To conclude, we sought out to understand if gastronomy has a primary or secondary role in this coastal region, determined by particular gastronomical aspects, in order to evaluate its recognition from both views, supply and demand.